The Effect of Hydrotherapy on Pain Intensity and Functional Ability in Lumbar Disk Herniation (LDH) Patients that Undergo Non-operative Procedure Pre-experimental Study at Medical Rehabilitation Installation of RSUP dr. Mohammad Hoesin Palembang - Theresa Rahmadhani; Nyimas Fatimah; Eka Febri Zullisetiana (Sriwijaya Journal of Medicine, 2020)
The effect of hydrotherapy on pain intensity and functional ability in lumbar disk herniation (LDH) patients that undergo non-operative procedure; pre-experimental study at medical rehabilitation installation of RSUP dr. Mohammad Hoesin Palembang. Lumbar disk herniation (LDH) is the most common disease that becaused low back pain and functional disability. Some studies mentioned that hydrotherapy is an effective treatment for low back pain.Therefore, this study was conducted to determine the effect of hydrotherapy on reducing pain intensity and improvingfunctional ability in LDH patients. This study was a pre-experimental study with one group pretest-posttest design. Data was collected by direct interviews to the patients using visual analogue scale (VAS) to measure pain intensity and Modified Oswestry Low Back Pain Disability Questionnaire to assess functional ability before and after underwent hydrotherapy once a week for 4 weeks. The data then undergo Shapiro-Wilk normality test and continue with Paired tTest or Wilcoxon test. From 30 subjects, it was found that there are effects of hydrotherapy on reducing pain intensity (p<0,001) and improving functional ability (p<0,001) in LDH patients that undergo non-operative procedure at the Medical Rehabilitation Installation of RSUP Dr. Mohammad Hoesin Palembang. There are effects of hydrotherapy on pain intensity and functional ability in LDH patients that undergo non-operative procedure.